Rheocarna Effectively Treats Oral Medicinal Therapy‐Resistant Cutaneous Symptoms and Renal Failure Induced by Cholesterol Crystal Embolism - Akinori Satake; Takahiro Tokuda; Hirofumi Ohashi; Yusuke Nakano; Akio Kodama; Tetsuya Amano (Clinical Case Reports)
ABSTRACT An 80‐year‐old man presented to our hospital with worsening renal function and ambulation difficulties due to lower extremity symptoms that included livedo reticularis, gangrene, cyanosis, and ulcers in his legs. The patient was diagnosed with a cholesterol crystal embolism. Treatment with prednisolone and rosuvastatin was initiated; however, no improvements were observed in the patient's cutaneous symptoms or renal function. Therefore, we decided to treat the patient with a new low‐density lipoprotein apheresis device (Rheocarna; Kaneka Corporation, Osaka, Japan). Following therapy, the lower extremity symptoms improved, and although dialysis was temporarily initiated, it was eventually discontinued.